Resocjalizująca rola sportu i rekreacji osób niedostosowanych społecznie = Resocializing role of sport and recreation of socially maladjusted people - Pierzchała, Kazimierz (Vilnius: Mykolas Romeris Universitetas)
Movement and physical fitness play a very important role in the life of every human being. Sports and recreational activities have long played a significant role in the institutional process of resocialisation of socially maladjusted people. These activities are eagerly supported by the educators of the institutions, and for the pupils are an excellent opportunity to demonstrate fitness, while rebounding accumulated tensions and frustrations.
Keywords: resocjalizacja; twórcza resocjalizacja; sport; rekreacja; niedostosowanie społeczne; zachowania dewiacyjne; aktywność ruchowa; kultura fizyczna; kreatywna zmiana; deprywacja sensoryczna; resocialization; creative rehabilitation; recreation; social maladjustment; deviant behaviour; physical activity; physical culture; creative change; sensory deprivation